URGENCY AND EMERGENCY IN OFFSHORE ENVIRONMENT: A CHALLENGE FOR NURSING CARE - Silva dos Santos, Ivanlésio; Paula de Paula Martins, Ana (Health and Society, 2023)
This is a descriptive study with a qualitative approach, based on articles available on the internet, where articles were found that report on the work performed by nurses in an offshore environment. The databases used were LILACS, BDEnf, SCIELO and academic Google, due to the low demand for published offshore nursing articles . A total of 387 publications were identified, of which only 35 were in full format, duplicate publications and those that did not meet the inclusion criteria were excluded, leaving only 15 articles as the final result. The data were distributed in a way to produce better understanding and comprehension. It is concluded that the role of the offshore nurse must be focused on managing the health of everyone who is present in the work environment, whether in a platform unit, ship or tug. This professional cannot just have a technical skill to work in this sector, as he works alone during boarding periods and in urgent and emergency situations, he needs attention, agility and attitudes that promote the well-being of the worker and/or his stability until arrival of air transport.